Experimental determination of the spectrum of structure vibrations under the influence of technological load - Vabischevich, Maksim; Dedov, Oleg; Glitin, Oleksandr (Technology audit and production reserves, 2019)
The object of research is the process of propagation of vibrations from technological equipment to the metal structures of a building. One of the problems in the inspection and monitoring of construction objects is the assessment of the vibrational impact of technological equipment on the load-bearing elements of the building. Existing regulatory documents and methods for accounting for dynamic impact fully cover this problem, as evidenced by the presence of emergency cases of operating structures that are subject to dynamic loads. The proposed approach, which is based on the hypothesis of considering the structure and technological equipment, has a dynamic impact as a single system with its corresponding dynamic characteristics. The implementation of this approach can be carried out by determining the integral dynamic parameters of the system with subsequent analysis and the establishment of causal relationships. During the study, records of continuous fixation of the parameters of the dynamic effect on the elements of the building structure, which are determined on the basis of preliminary analysis, were used. As a result of the analysis of the vibrograms, the vibrational spectra of the structure are constructed, from which the dominant vibrational frequencies of 3.470 and 3.625 Hz are determined. The established frequencies correspond to the main frequencies and their harmonics of the technological process implementation according to the technical characteristics of the equipment, amount to 3.670 Hz. The discovered phenomena of the internal resonance of the general construction system of the technological workshop make it possible to clearly formulate the causes of the appearance of excessive vibrations. Experimental studies of the influence of technological equipment on the frame of the structure are carried out. A finite element model of the frame based on an instrumental examination of the building is developed. The obtained research results can be used to develop methods and technologies for diagnosing and establishing the causes of excessive fluctuations in the supporting and enclosing structures of structures under the action of a dynamic load of technogenic origin.